The Impact of Health-Related Quality of Life and Comorbidities in Chronic Kidney Disease: A Hospital-Based Cross-Sectional Study - Biju , Blessy; D’cruz, Adlin; Jiby , Sneha; Devassy , Melvin; Jacob , Rosmin (Journal of Drug Delivery and Therapeutics, 2025)
Background: Chronic kidney disease (CKD) is a primary global health concern, often progressing silently and leading to severe complications in later stages.Methods: A hospital-based cross-sectional study was conducted over six months among 196 CKD patients (stages 3–5D) at a tertiary care hospital. Health-related quality of life (HRQoL) was assessed using the validated Malayalam version of the KDQOL-SF™ 1.3 questionnaire. Sociodemographic, clinical, and biochemical data were collected, and CKD staging was based on the CKD-EPI equation. The impact of 12 common comorbidities was analyzed using patient history, clinical evaluation, and laboratory data. Statistical analysis included ANOVA, chi-square tests, Pearson’s correlation, and logistic regression, with p < 0.05 considered statistically significant.Results: Quality of life (QOL) declined notably as CKD progressed from stage 3 to stage 5, with stage 5 patients exhibiting higher creatinine, lower hemoglobin, and increased serum uric acid and urea levels. HRQoL scores, measured by KDQOL-SF 1.3, worsened across all dimensions, with stage 3 patients having higher SF-36 scores than those in stages 4 and 5. Comorbidities such as hypertension, diabetes, hyperlipidemia, and heart issues were prevalent and significantly impacted CKD progression. Regression analysis highlighted that age above 55, proteinuria, hyperuricemia, unhealthy BMI, and lower GFR were linked to having multiple comorbidities in CKD patients, accelerating progression to stage 5 and increasing treatment burdens.Conclusion: Chronic kidney disease (CKD) significantly impairs health-related quality of life, with the impact intensifying in advanced stages and in the presence of multiple comorbidities.Keywords: chronic kidney disease, diabetes, hypertension, quality of life